Soft Translations and Soft Extensions of BCI/BCK-Algebras - Nazra Sultana; Nazia Rani; Muhammad Irfan Ali; Azhar Hussain (The Scientific World Journal)
The concept of soft translations of soft subalgebras and soft ideals over BCI/BCK-algebras is introduced and some related properties are studied. Notions of Soft extensions of soft subalgebras and soft ideals over BCI/BCK-algebras are also initiated. Relationships between soft translations and soft extensions are explored.